Troubling ideas for widening participation: how higher education institutions in England engage with research in their access agreements. (30th June 2016) - Wardrop, Alex; Hutchings, Maggie; Collins, Bethan; Eccles, Sue; Heaslip, Vanessa; Hunt, Clive; Pritchard, Colin
This article explores how higher education institutions in England engage with research in their access agreements. Through an analysis of access agreements from 2014-15 to 2016-17, a picture of how research is understood, undertaken and documented emerges. A lexical analysis of the texts was used to establish the different ways research is being referred to or funded as part of the access agreement process. The analysis shows a productive relationship between national policy and institutional activity. But there appears to be a lack of infrastructure at an institutional and sector level to join up sustained and rigorous research with widening participation activity and policy. This means that, even after ten years of access agreements, widening participation is not fully embedded into the academic practice of higher education. We argue that research undertaken as part of the access agreement process can provide much needed evidence of impact and situate activity within an institution-wide context. However, we also suggest that widening participation research has the potential to offer productive troubling ideas to dominant rhetoric and, in so doing, shape new ways of thinking about, and doing, widening participation within institutions and across the sector.